To Determine the Frequency of Indication of Emergency Peripartum Hysterectomy - NUZHAT MALIK, ZOHRA KHANUM, SANA MARYAM, ASIA PARVEEN (Journal of Fatima Jinnah Medical University, 2018)
Introduction: Peripartum or Emergency obstetric hysterectomy is defined as hysterectomy performed within 24 hours of a delivery. It includes both postpartum and cesarean hysterectomy. It is a life saving procedure although it is opted as a desperate attempt when all measures fail to control catastrophic hemorrhage from placental bed in placenta previa or morbid adherence of placenta or due to uterine atony. Common indications for emergency peripartum hysterectomy include uterine rupture and uterine atony. Objective: To determine the frequency of various indications of emergency peripartum hysterectomy in a tertiary care hospital Study Setting: Obstetrics and Gynaecology department, Sir Ganga Ram Hospital, Lahore Study Design: Cross sectional study Study Duration: One Year From:01-01-2015to31-12-2015 Material & Methods: A total of 45 cases between 20 – 40 years, and gestational age >25 week to 40 week assessed by ultrasound with primary post partum haemorrhage with singleton pregnancy on ultrasound were included in the study through emergency department in Sir Ganga Ram Hospital Lahore, while Peripartum hysterectomy due to cancer and patients having coagulopathy due to liver disease or bleeding disorder diagnosed with history and investigation (bleeding time, Clotting time, Platelet count, prothrombin time/activated partial thromboplastin time) were excluded. All data of patients was entered on pre-designed proforma. Procedure was performed by consultant obstetrician after taking written informed consent and different indications of peripartum hysterectomy were entered in proforma. The indications of hysterectomy i.e. rupture of uterus, uterine atony and morbidly adherent placenta were recorded. Conclusion: We concluded that rupture of uterus and uterine atony are the common indications of peripartum hysterectomy followed by morbidly adherent placenta in patients coming to our hospital. These results are helpful for obstetricians while dealing with this morbidity.